Genetic Diversity and Population Structure Analysis of Excellent Sugar Beet (Beta vulgaris L.) Germplasm Resources - Fei Peng; Zhi Pi; Shengnan Li; Zedong Wu (Horticulturae, 2024)
This study analyzed the genetic diversity, population structure, and cluster analysis of 129 sugar beet germplasm resources to screen superior germplasms for breeding using the 27 simple sequence repeat (SSR) and 33 pairs of insertion–deletion (InDel) molecular markers. After integrating the phenotypic variation of 16 descriptive and 4 qualitative phenotypic variables, the genetic variation levels of the 129 sugar beet germplasms’ phenotypic traits were analyzed using the principal component analysis (PCA), correlation analysis, and analysis of variance methods. The genetic diversity examination of molecular markers showed a polymorphism information content (PIC) of 0.419–0.773 (mean = 0.610). Moreover, the mean number of effective alleles detected via the SSR and InDel markers was 3.054 and 2.298, respectively. Meanwhile, the PIC ranged from 0.130 to 0.602 (mean = 0.462). The population structure analysis revealed the most appropriate K-value, indicating three populations (K = 3). The genetic distances of the 129 germplasm resources ranged from 0.099 to 0.466 (mean = 0.283). The cluster analysis results demonstrated that the germplasms were grouped into three primary classes. Based on the analysis of variance, the two qualitative features with the highest coefficients of variation were petiole width (16.64%) and length (17.11%). The descriptive trait root length index (1.395) exhibited the greatest genetic diversity. The PCA reduced the 20 phenotypic traits into five principal components, contributing 51.151%. The results of this study provide a theoretical foundation for the future selection and breeding of superior sugar beet germplasm resources.